EFEKTIFITAS GUIDED IMAGERY DAN SLOW DEEP BREATHING TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI RSUD dr. R. SOEDARSONO PASURUAN - Dzurrotun Nafiah; Sumirah Budi Pertami; mustayah . (Poltekkes Kemenkes Malang, 2020)
Hypertension is one of the most influential risk factors for the incidence of heart disease and blood vessels. Lack of knowledge about the management of hypetension is a contributing factor. The purpose of this study is to determine The Effectiveness of Guided Imagery and Slow Deep Breathing Against the Decline of Blood Pressure on the Patient Hypertension. This research uses Quasi Experimental Design design withdesign non equivalent pretest posttest design and Group Comparasion, with consecutive sampling technique, great samples 30 respondents divided into 2 groups namely Guided Imagery and Slow Deep Breathing. Each group received treatment for 15 minutes once a day for three days, each treatment performed before and after the blood pressure measurement. The results of this study used dependent t test, wilcoxon sign rank test, two samples independent t test, and U Mann Whitney test showed that diatolic systolic blood pressure in each group decreased, in Guided Imagery 4.07 mmHg and 3.4 mmHg (p value sebesar 0,000), Slow Deep Breathing 8 mmHg and 6.8 mmHg (p value sebesar 0,000 , 0.001). It was concluded that Slow Deep Breathing is more effective than Guided Imagery in lowering blood pressure in hypertensive patients. As nurses are expected to apply nonpharmacology like a Guided Imagery and Slow Deep Breathing as a pharmacological companion therapy in blood pressure.